Sports sponsorship and the impact on a brand's purchasing intention and recommendation: Red Bull, more than wings - Brito, David Coelho (2019)
Sponsorship has proven to be a fast-flourishing marketing tool. Its main essence is, in the companies' perspective, to effectively promote their products and services. Therefore, over the years, companies have begun to behold and consider this tool as a massive gateway for a successful strategical long-term plan. Previous sponsorship studies, have instigated to examine its concept on multiple situations and the implications they entail, but often lack new effective measures and approaches. Hence, the purpose of this investigation is to better understand and scrutinize the effects of Sports Sponsorship - its Awareness, Perceived Quality and Image - on Brand Equity variables, in particular, on Brand Image, Brand Awareness, Brand Loyalty and Perceived Brand Quality. Consequently, with that in mind, there is an examination of the effect/influence on the consumer's Brand Purchasing Intention and Brand Recommendation. Moreover, Red Bull, is used as a main reference. The energy drinks' company was placed on a Sports Sponsorship context, with 3 main sports highlighted (Football/Soccer, Air Racing and Formula 1). The respondents (from a diverse age range), were asked several questions considering Sponsorship and Brand Equity's variables and, their a-posteriori Brand Purchasing Intention and Recommendation - always heeding the Brand´s Sports Sponsorship they consider to be the most important. The results gathered by the following research propose that the presence of a Sports Sponsorship initiative brings no direct influence on a Brand's Purchasing Intention and Recommendation. In addition, Perceived Brand Quality affects both final variables, whereas Brand Awareness impacts none.